A review of different catalytic systems for dry reforming of methane: Conventional catalysis-alone and plasma-catalytic system. Issue 46 (April 2021) - Shi, Cong; Wang, Sha; Ge, Xiang; Deng, Shengxiang; Chen, Bin; Shen, Jun
Highlights: Status of different catalytic system for DRM is overviewed. The main factors affecting the conventional catalysis-alone system are evaluated. In the plasma-catalytic system, the cold and thermal plasma-catalytic systems are discussed respectively. The mechanism of plasma-catalyst interaction is reviewed. The conventional catalysis-alone system and plasma-catalytic system are compared. Abstract: Dry reforming of methane (DRM) uses methane (CH4 ) and carbon dioxide (CO2 ) as raw materials to produce syngas, which has unique economic and environmental benefits. However, DRM reaction still faces the disadvantages of catalyst sintering deactivation and carbon formation. In this paper, the research progress of different DRM catalytic systems is reviewed. The conventional catalysis-alone system, plasma-catalytic system and some other catalytic systems are discussed. The key factors affecting the performance evaluation of the catalyst in the conventional catalysis-alone system were given. In particular, whether the plasma-catalytic system can achieve higher conversion than the conventional catalysis-alone system has become the focus of attention. For this reason, the reactor structure, discharge mode and the combination with catalyst were discussed. The mechanism of plasma-catalyst interaction was discussed through literature review. In addition, the possibility of other applications of DRM plasma-catalytic system is also considered. Finally, the advantages and disadvantages of conventional catalysis-alone system and plasma-catalytic system are compared. Some other catalytic systems, such as catalytic membrane reactor and solar driven methane reforming, are also introduced. Considering the research status of DRM, we can further improve the conversion and energy conversion efficiency by improving the DRM catalyst and optimizing the design of plasma reactor.